The Use Of Feed Technology Of Local Based Source To Support The Productivity Of Beef Cattle In West Sumatra - . buharman (Indonesian Center for Animal Research and Development, 2011)
The use of feed technology of local based sources to support beef cattle productivity is the key of the successful PSDS/K program in 2014. In 2009, the cattle population in West Sumatra was about 492,272 heads, and the population growth during 2005 – 2009 was about 6.1 percent per year are the growth of cattle slaughtered for local consumption was around 11.0 percent or about 86,028 heads/year. The rate of population growth is much lower than the target of PSDS/K 2014 which around 12.5 percent. The source of feedstuffs come from native grass and by product of agro-industry. These agro-industry by products such as rice, maize, cassava, palm oil, cacao, coffee by products have big potential for feed which account for supporting 1.75 to 2.1 million animal unit. These by-products mostly used for feed supplement by simple process technology. The role of institution like LM3 and SMD can be optimized to support local feed supply which available on location either for local cattle consumption or for commercial use. Key words: Technology, feed, agricultural byproduct, beef cattle